STRATEGI PENINGKATAN MOTIVASI BERPRESTASI DAN DISIPLIN GURU PADA SMP NEGERI 1 BESULUTU - Sarni Sarni; Samdin Samdin; La Hatani; Murdjani Kamaluddin; Aidin Hudani Awasinombu; La Ode Asfahyadin Aliddin (Pascasarjana Universitas Halu Oleo, 2020)
This study aims to determine and analyze strategies to improve achievement motivation and discipline of teachers of SMP Negeri 1 Besulutu Konawe Regency. This research uses a descriptive qualitative approach. Data collected through observation, interviews and documentation. The results of this study indicate that in an effort to improve achievement motivation and teacher discipline in SMP Negeri 1 Besulutu using strategies: planning, implementation and evaluation. Achievement motivation and teacher discipline are two very important things that must be attached to an educator in an effort to realize educational goals to shape and produce students who excel and discipline.